Information needs and patterns of information and library use of college faculty and college senior students of ViSCA a survey with implications for collection development - Napiere, Rebecca B. (1980)
This survey was conducted to find out the information needs and patterns of information and library use of the college faculty and college senior students of ViSCA, and the implications of such needs to collection development in the ViSCA Library.